Erythroferrone derived from osteoblasts regulates stress erythropoiesis - Pinanong Na-Phatthalung; Gabrielle van Caloen; Marina Planoutene; Emily Tai; Anisa Gumerova; Ronit Witztum; Eva Ingber; Leon Kautz; Farhath Sultana; Funda Korkmaz; Maayan Levy; Tony Yuen; et al. (Proceedings of the National Academy of Sciences, 2026)
Erythroferrone (ERFE), secreted by erythroblasts, is regarded as a classical regulator of iron metabolism through its suppression of hepcidin. Thus, as a consequence of insufficient hepcidin suppression and reduced iron availability, global Erfe – / – mice exhibit delayed recovery after phlebotomy. We have shown previously that, apart from erythroblasts, ERFE is notably expressed in osteoblasts. To explore the effect specifically of osteoblast-derived ERFE during stress erythropoiesis, we first created Erfe fl/fl mice, which were then crossed with Col2.3 -Cre mice to generate osteoblast-selective Erfe mutants (or Col2.3 -Cre; Erfe fl/fl mice). The induction of stress erythropoiesis in these latter mice by phlebotomy resulted in reduced serum ERFE levels and increased liver Hamp (hepcidin) expression. Importantly, Col2.3 -Cre; Erfe fl/fl mice showed a more robust red blood cell (RBC) recovery 6 d postphlebotomy, with no differences in bone marrow Erfe relative to Erfe fl/fl mice. Furthermore, despite no differences in the baseline RBC count, reticulocyte count, spleen size, or bone marrow cellularity, osteoblast-selective ERFE loss resulted in enhanced erythropoietin receptor ( Epor ) and bone morphogenetic protein 4 ( Bmp4 ) expression in whole bone in vivo and in osteoblasts ex vivo. Finally, the osteoblast-selective Erfe mutants showed erythroid lineage proliferation and enhanced EPO responsiveness in a BMP4-dependent manner. Taken together, we posit that ERFE loss specifically from osteoblasts enhances RBC recovery during stress erythropoiesis—defining mechanisms of regulation in the crosstalk between osteoblasts and erythroblasts.